Konsep Keadilan Restoratif dalam Jinayah Islam dan Implementasinya pada Sistem Peradilan Indonesia - Cut Nurita (Universitas Medan Area, 2026)
This study discusses the concept of restorative justice in Islamic jurisprudence and its relevance to the implementation of the criminal justice system in Indonesia. Restorative justice, which emphasizes the recovery of victims' losses, the responsibility of the perpetrators, and social reconciliation, is gaining increasing attention in Indonesia's criminal law reform. Although considered a modern approach, restorative principles have actually long been part of Islamic criminal law through the concepts of islah (peace), diyat (compensation), and 'afw (forgiveness). This study uses a juridical-normative method with a qualitative approach to analyze the sources of Islamic law, the doctrine of fiqh jinayah, and national regulations related to restorative justice. Data was obtained through literature studies on the Qur'an, hadiths, fiqh books, laws and regulations, and various scientific journals. The results of the study show that there is a substantive conformity between restorative values in Islamic law and the restorative justice paradigm that is developing in Indonesia. Indonesia has adopted a restorative approach through the Juvenile Criminal Justice System Law, Perpol No. 8 of 2021, the Prosecutor's Office's guidelines, and Supreme Court policies. However, its implementation still faces obstacles in the form of inuniform practices, limitations of comprehensive regulations, and potential abuse of discretion. This study concludes that Islamic jinayah values can strengthen the philosophical and moral legitimacy of the application of restorative justice in Indonesia, as well as provide a normative basis for a more humanistic and restorative-oriented criminal law reform. The integration of Islamic concepts and national legal policies has the potential to produce a justice system that is more just, responsive, and in accordance with the character of Indonesian society